Pengaruh Pelatihan, Pengembangan Karir, Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Labuhanbatu - Gulo, Nur’ainun; Siregar, Nurintan Asyiah (Jurnal Penelitian Multidisiplin Ilmu, 2024)
The purpose of this study was to determine the effect of training, career development, work motivation and job satisfaction on employee performance at the Population and Civil Registration Office of Labuhanbatu Regency. The research method uses multiple linear regression analysis which is processed using SmartPLS3. The results of the study prove that the variables of training, career development, work motivation and job satisfaction have a significant effect on performance. The R Square value is 0.812 or 81.20% of the Training, Career Development, Work Motivation and Job Satisfaction variables affect employee performance while the remaining 18.80% is influenced by other factors.